2021
DOI: 10.1007/s10143-021-01672-5
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial aneurysm wall (in)stability–current state of knowledge and clinical perspectives

Abstract: Intracranial aneurysm (IA), a local outpouching of cerebral arteries, is present in 3 to 5% of the population. Once formed, an IA can remain stable, grow, or rupture. Determining the evolution of IAs is almost impossible. Rupture of an IA leads to subarachnoid hemorrhage and affects mostly young people with heavy consequences in terms of death, disabilities, and socioeconomic burden. Even if the large majority of IAs will never rupture, it is critical to determine which IA might be at risk of rupture. IA (in)s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 111 publications
0
4
0
Order By: Relevance
“…(Kormanz). Along the same lines, Morel et al found that unruptured intracranial aneurysmal walls display a significantly lower expression of inflammatory cluster differentiation (CD68) positive cells, suggestive of macrophages, thereby lending support to the role of a sustained macrophage influx as critical effectors in progressive aneurysmal remodeling, growth and subsequent rupture [48]. In addition to direct histological evidence documenting a sparse inflammatory cell invasion in unruptured intracranial aneurysmal models, radiologic studies further substantiate such observations by documenting changes in aneurysmal wall enhancement.…”
Section: Unruptured Cerebral Aneurysms: Induction Of Inflammatory Gen...mentioning
confidence: 89%
“…(Kormanz). Along the same lines, Morel et al found that unruptured intracranial aneurysmal walls display a significantly lower expression of inflammatory cluster differentiation (CD68) positive cells, suggestive of macrophages, thereby lending support to the role of a sustained macrophage influx as critical effectors in progressive aneurysmal remodeling, growth and subsequent rupture [48]. In addition to direct histological evidence documenting a sparse inflammatory cell invasion in unruptured intracranial aneurysmal models, radiologic studies further substantiate such observations by documenting changes in aneurysmal wall enhancement.…”
Section: Unruptured Cerebral Aneurysms: Induction Of Inflammatory Gen...mentioning
confidence: 89%
“…Incorporating vascular wall MRI into the diagnostic algorithm might greatly improve the ability to identify the site of the ruptured aneurysm, hence optimizing the surgical strategy to minimize further bleeding and optimize patient outcomes. 16 , 17…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of intracranial aneurysm (IA) is highly complex [1] . Several studies emphasized the role of wall shear stress (WSS) in endothelial cell (EC) dysfunction and IA initiation and growth [2] , [3] , [4] , [5] , [6] .…”
Section: Introductionmentioning
confidence: 99%